Peran Kadar Vitamin D Darah terhadap Derajat Keparahan Klinis Pasien Bell’s Palsy - Sinta, Mutia; Sulistyani, Sulistyani; Ratnasari, Yuhanida; Milyarona, Fitri Pranita (Penerbit Goodwood, 2023)
Purpose: This study aims to determine the effect of blood vitamin D levels on clinical severity in patients with Bell's palsy. Methodology/approach: The study was conducted with longitudinal observational analytic on patients with Bell’s palsy. Vitamin D levels in the form of 25-hydroxyvitamin D (25(OH)D were measured in each subject. The clinical severity was evaluated using the House-Brackmann grading. Results/findings: A total of 20 patients (10 women, 10 men, mean age 48.8 ± 12, 97 years, range 22-72 years) were evaluated between March-July 2022. Vitamin D deficiency was present in 13 (65%) patients, insufficiency in 7 (35%) patients, and no normal blood vitamin D levels were found in patients with Bell’s palsy. Two (10%) patients with grade 3 Bell’s palsy, six (30%) grade 4 patients, and twelve (60%) grade 5 patients. Results showed higher clinical severity had lower vitamin D levels. Statistical analysis showed a significant difference with p value = 0.003. Limitations: The research that discusses the dosage, method, and duration of vitamin D administration in patients with Bell's palsy still very limited. Contribution: With further research, it can be proven vitamin D deficiency can be associated with Bell's palsy, so appropriate treatment and prevention can be given.